Effect of sodium stibogluconate in recruiting and awakening immune cells in the pleural fluid of pancreatic cancer: preparation for immunotherapy - Yu, Baofa; Jing, Peng; Gao, Feng; Zhang, Peicheng; Zheng, Guoqin; Zhang, Xiaomin (Frontiers in Immunology, 2024)
The study provides evidence to support possible precision immunotherapy with sodium stibogluconate, a protein tyrosine phosphatase inhibitor, as an immune booster that can potentially be applied to treatment for pleural fluid of pancreatic cancer.Single-cell RNA sequencing (scRNA-seq) is used to profile the immune reaction induced by hapten enhanced local chemotherapy. Important changes of the immune response at both the cellular and molecular levels are seen following sodium stibogluconate injection into pleural fluid of pancreatic cancer.